The Effect of Bed Catalyst Design Variation on Catalytic Converter against Exhaust Emission Level of Carbon Monoxide (CO) and Hydrocarbon (HC) in Gasoline Engine - Arianto, Riky; Nauri, Imam Muda (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
The increasing motor vehicle in Indonesia causes air pollution. Several gases that arise as pollutants are carbon monoxide (CO), hydrocarbon (HC), nitrogen oxides (NOx). This study aimed to determine the effect of catalyst bed design variation on catalytic converter on exhaust emissions of carbon monoxide and hydrocarbons in gasoline engine. The method used in this study was to compare the level of exhaust emissions with and without application of bed catalyst variation by putting hole on all of bed catalyst part, putting hole on the middle and side of bed catalyst part, and putting hole on the top and bottom part of bed catalyst part. The results showed that the lowest level of CO was on sample without catalyst, with value of 1.6%vol at 1500 RPM. While the result with variation hole on bed catalyst showed that the CO level on of full hole was 3.01%vol at 1500 RPM, hole on the middle and side was 3.19%vol at 1500 RPM, and hole on the top and bottom was 1.93%vol at 1500 RPM. Meanwhile, the lowest decreasing of HC level was found on the sample without catalyst, with the value of 155 ppm at 8000 RPM. Whereas the result with variation hole on the bed catalyst showed that the HC level on full hole variation was 543 ppm at 7500 RPM, hole on the middle and side was 459 ppm at 6500 RPM, and hole on the top and bottom was 509 ppm at 7500 RPM.